An interview study of pregnant women who were provided with indoor air quality measurements of second hand smoke to help them quit smoking. Issue 1 (December 2016) - Morgan, Heather; Treasure, Elizabeth; Tabib, Mo; Johnston, Majella; Dunkley, Chris; Ritchie, Deborah; Semple, Sean; Turner, Steve
Abstract Background Maternal smoking can cause health complications in pregnancy. Particulate matter (PM2.5 ) metrics applied to second hand smoke (SHS) concentrations provide indoor air quality (IAQ) measurements and have been used to promote smoking behaviour change among parents of young children. Here, we present the qualitative results from a study designed to use IAQ measurements to help pregnant women who smoke to quit smoking. Methods We used IAQ measurements in two centres (Aberdeen and Coventry) using two interventions: 1. In Aberdeen, women made IAQ measurements in their homes following routine ultrasound scan; 2. In Coventry, IAQ measurements were added to a home-based Stop Smoking in Pregnancy Service. All women were invited to give a qualitative interview to explore acceptability and feasibility of IAQ measurements to help with smoking cessation. A case study approach using grounded theory was applied to develop a typology of pregnant women who smoke. Results There were 39 women recruited (18 in Aberdeen and 21 in Coventry) and qualitative interviews were undertaken with nine of those women. Diverse accounts of smoking behaviours and experiences of participation were given. Many women reported changes to their smoking behaviours during pregnancy. Most women wanted to make further changes to their own behaviour, but could not commit or felt constrained by living with a partner or family members who smoked. Others could not envisage quitting. Using themes emerging from the interviews, we constructed a typology where women were classified as follows: 'champions for change'; 'keen, but not committed'; and 'can't quit, won't quit'. Three women reported quitting smoking alongside participation in our study. Conclusions Pregnant women who smoke remain hard to engage, . Although providing IAQ measurements does not obviously improve quit rates, it can support changes in smoking behaviour in/around the home for some individuals. Our typology might offer a useful assessment tool for midwives.